"Do it this way, not that way": An exploration of Chinese workplace conflicts. Issue 2 (10th April 2017) - Guo, Yijia; Cionea, Ioana A.
Abstract : Purpose: This paper aims to examine the occurrence and management of conflict in Chinese organizations, from an emic perspective. The authors provide an in-depth understanding of Chinese working adults' lived experiences regarding workplace conflicts. Design/methodology/approach: The study is a qualitative one, consisting of open-ended questionnaires administered to 55 Chinese nationals who worked in governmental, public or international organizations in China. A thematic analysis of the answers was conducted. Findings: Chinese participants adopted a normative mental model that defined their preferred "way of doing" things. A skillful balance was expected in conflict management that incorporated integrated open communication and strategic silence. Chinese working adults emphasized maturity in the workplace and the recognition of shared goals. Research limitations/implications: The online questionnaire format may have constrained participants' responses. Also, the data were collected from various organizational contexts, but there were not enough participants from each type of organization so that comparisons between institutions could be made. Practical implications: The results could help expatriate populations better prepare their lives abroad in China. Also, the findings could aid organizational or management consultants who work closely with Chinese partners. Social implications: The findings enhance our understanding of how Chinese working adults deal with workplace conflicts and the circumstances in which conflicts arise in the workplace, which also reflected the social and cultural contexts of the Chinese workplace experience. Originality/value: This study provides an alternative interpretation of workplace conflicts and their management in China that is anchored in the unique organizational and national cultural context. They constitute the base for future development of culture-based explanations of Chinese organizational conflict behaviors.